Business Consulting para ETRACONSAN S.A. - Ccama Mamani, Vicki Lizet (2025)
ETRANSCONSTRUC SANTIAGO SOCIEDAD ANÓNIMA, hereinafter ETRACONSAN S.A., is a company dedicated to the rental of heavy machinery and the sale of fuels, was established in 2009, with 51 shareholders, in 2012 the inclusion of new shareholders was approved, reaching 70 shareholders to date, its commercial area is located in Ananea, its main customers are the mining cooperatives in the area, they also rent to construction sites. The objective of the Business Consulting is to know the problems that the company has, problems that prevent it from continuing to grow and generating greater profitability, in order to make a diagnosis of the company, several interviews were conducted with key personnel of the company, staff of the managements that carry out the operations of the company; SWOT analysis, AMOFHIT analysis, PESTEL analysis, MEFE and MEFI analysis, among other methods, were also carried out, reaching the conclusion that the company suffers from different problems, such as lack of control in fuel management, poor management in the logistics chain, and lack of processes, generating unnecessary costs; therefore, it was defined that the main problem is the poor management of the logistics chain in the sale of fuels. For which an implementation plan was made to solve the problem, which is the implementation of a process manual and the implementation of an ERP, whose investment would be S/ 151,514. The proposed investment is possible, given that the NPV and IRR analyses were carried out, which gave data of S/ 3'588,150 and IRR of 46%, which is higher than the estimated CAPM discount rate of 24.81%, indicating a high profitability in the proposal, the investment will be recovered in 4 years. Likewise, a Monte Carlo simulation was performed, where 100 simulations of 10,000 iterations were made, observing that the NPV is S/ 3'431,492, being lower than the calculation made, with prices that are between S/ 13.19 and S/ 22.69 for Diesel B5 S-50 UV, concluding that the NPV has been overestimated.